Zirconium-based MOFs-loaded ionic liquid-catalyzed preparation of biodiesel from Jatropha oil - Dai, Qiqi; Yang, Zifei; Li, Jin; Cao, Yang; Tang, Hongbiao; Wei, Xiaocui (Renewable energy, 2021)
An environmentally acidic ionic liquid was prepared with 1-methyl-imidazole, 1,3-propyl sultone and H2SO4, and successfully loaded B acidic ionic liquid into three zirconium-based MOFs to synthesize the catalyst used to prepare biodiesel from Jatropha oil by impregnation method. The structure of the catalyst was characterized by XRD, SEM, FTIR and BET. Compare the activities of the three catalysts (through PSH/UiO-66, PSH/UiO-66NO2, PSH/UiO-66-NH2) experiments, the catalytic activity of PSH/UiO-66-NO2 was found to be the highest, and the conversion rates of Jatropha oil was 96.69%. The effect of methanol oil mole ratio, catalyst dosage, reaction temperature, and reaction time on the conversion of Jatropha oil to biodiesel was investigated, an orthogonal test determined the optimum reaction conditions of using PSH/UiO-66-NO2 catalyst. The optimal reaction conditions were obtained: reaction temperature was 343 K, catalyst dosage to oil was 4 wt%, methanol to oil ratio was 25:1, reaction time was 4 h, and the average conversion rates of Jatropha oil was 97.57%, the methyl ester rate was over 99.98%. The results showed that the four reaction factors had significant effects on the Jatropha oil conversion rates: reaction time > catalyst dosage > reaction temperature > methanol to oil ratio. •A desirable loading of ionic liquid was achieved due to UiOs the large surface area.•The novel PSH immobilization on UiOs has been synthesized, and the activity of PSH/UiO-66 is higher than the UiO-66 and PSH.•One-pot method produces biodiesel from jatropha oil, methyl ester rate was 99.98%.•Under the optimal conditions, a high conversion rates of Jatropha oil was 97.57% as obtained from jatropha oil. .